2006
DOI: 10.4049/jimmunol.176.1.173
|View full text |Cite
|
Sign up to set email alerts
|

The Glycosaminoglycan-Binding Domain of Decoy Receptor 3 Is Essential for Induction of Monocyte Adhesion

Abstract: Decoy receptor 3 (DcR3), a soluble receptor for Fas ligand, LIGHT (homologous to lymphotoxins shows inducible expression and competes with HSV glycoprotein D for herpes virus entry mediator, a receptor expressed by T lymphocytes), and TNF-like molecule 1A, is highly expressed in cancer cells and in tissues affected by autoimmune disease. DcR3.Fc has been shown to stimulate cell adhesion and to modulate cell activation and differentiation by triggering multiple signaling cascades that are independent of its thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 47 publications
1
47
0
3
Order By: Relevance
“…Імовірно, що цитоплазматичні глікопротеїни з молекулярними масами 34, 30, 22 кДа відповідають азуроцидину, еластазі та катепсину G, функція яких пов'я-зана з бактерицидною та фагоцитарною ак-тивністю лейкоцитів. Виявлене нами зменшення інтенсивності лектинореактивної смуги, яка свідчить про експонування інтегрину p150,95 (CD11c/ CD18), може бути причиною зниження показників агрегації за наявності лектину RСА, оскільки відомо, що активація агрегації НГ відбувається за допомогою приєднання С3b-компонента комплементу до вказаного рецептора [12]. Не виключено також, що пригнічення бактерицидної активності ней-трофілів за умов ЦД 1-го типу, встановлене нами раніше [2], пов'язане зі зниженням вмісту катепсину G, азуроцидину, лейкоци-тарної еластази та рецептора CD88 [10,18,24], молекулярні маси яких відповідають ви-явленим і проаналізованим лектинореактив-ним бендам.…”
Section: результати та їх обговоренняunclassified
“…Імовірно, що цитоплазматичні глікопротеїни з молекулярними масами 34, 30, 22 кДа відповідають азуроцидину, еластазі та катепсину G, функція яких пов'я-зана з бактерицидною та фагоцитарною ак-тивністю лейкоцитів. Виявлене нами зменшення інтенсивності лектинореактивної смуги, яка свідчить про експонування інтегрину p150,95 (CD11c/ CD18), може бути причиною зниження показників агрегації за наявності лектину RСА, оскільки відомо, що активація агрегації НГ відбувається за допомогою приєднання С3b-компонента комплементу до вказаного рецептора [12]. Не виключено також, що пригнічення бактерицидної активності ней-трофілів за умов ЦД 1-го типу, встановлене нами раніше [2], пов'язане зі зниженням вмісту катепсину G, азуроцидину, лейкоци-тарної еластази та рецептора CD88 [10,18,24], молекулярні маси яких відповідають ви-явленим і проаналізованим лектинореактив-ним бендам.…”
Section: результати та їх обговоренняunclassified
“…DcR3 is believed to block the cellular effects caused by the binding of these ligands to their membrane-bound cognate receptors by blocking ligand/receptor binding, as shown for the binding of FasL to Fas and TL1A to death receptor 3 (1,3,4). It has recently been reported that, in addition to binding to these ligands, DcR3 may bind to, and cross-link, proteoglycans to induce monocyte adhesion (5).…”
Section: Ecoy Receptor 3 (Dcr3)mentioning
confidence: 99%
“…Gal-1-Fc or W69G-Fc fusion proteins were overexpressed using the FreeStyle 293 expression system as reported (30). Briefly, 30 g pSecTaggalectin-1-hIgGFc m or pSecTagW69G-hIgGFc m was used to transfect 3 ϫ 10 7 293F cells with 293fectin.…”
Section: Production Of Gal-1-fc and W69g-fc Fusion Proteinmentioning
confidence: 99%